Predisposition to cancer in children and adolescents. (February 2021) - Kratz, Christian P; Jongmans, Marjolijn C; Cavé, Hélène; Wimmer, Katharina; Behjati, Sam; Guerrini-Rousseau, Lea; Milde, Till; Pajtler, Kristian W; Golmard, Lisa; Gauthier-Villars, Marion; Jewell, Rosalyn; Duncan, Catriona; et al.
Summary: Childhood malignancies are rarely related to known environmental exposures, and it has become increasingly evident that inherited genetic factors play a substantial causal role. Large-scale sequencing studies have shown that approximately 10% of children with cancer have an underlying cancer predisposition syndrome. The number of recognised cancer predisposition syndromes and cancer predisposition genes are constantly growing. Imaging and laboratory technologies are improving, and knowledge of the range of tumours and risk of malignancy associated with cancer predisposition syndromes is increasing over time. Consequently, surveillance measures need to be constantly adjusted to address these new findings. Management recommendations for individuals with pathogenic germline variants in cancer predisposition genes need to be established through international collaborative studies, addressing issues such as genetic counselling, cancer prevention, cancer surveillance, cancer therapy, psychological support, and social-ethical issues. This Review represents the work by a group of experts from the European Society for Paediatric Oncology (SIOPE) and aims to summarise the current knowledge and define future research needs in this evolving field.